Emerging Challenges and Prospects of Digital Transformation and Stakeholders Integration in Urban Land Administration in Ethiopia. (September 2021) - Gebrihet, Hafte Gebreselassie; Pillay, Pregala
There is global consensus on the need for information and communication technology (ICT) to support digital transformation in public administration. This is specifically true in decentralized public administration, where the stakeholders need a modern technology that integrates them. This study examines the emerging challenges and prospects of digital transformation and the stakeholders' integration in urban land administration in Mekelle City, Ethiopia. An interpretive paradigm, qualitative analytical method, and case study strategy were adopted for this study. A total of 78 interviewees comprising 30 auctioneers, 20 experts, 20 officials, 4 judges, and 4 prosecutors participated based on the data saturation principle. The study revealed that digitalized land administration offers opportunities to reduce civil servants' workload, improve cost-effective service delivery, and enhance trust between the municipal government and its clients. However, the system of urban land administration in the city is not digitalized due to financial limitations and leadership challenges. Furthermore, this study revealed a low level of stakeholders' integration in Mekelle due to the lack of proper implementation of e-government, e-service, and e-participation, including lack of commitment by the stakeholders. Thus, a non-digitalized land administration system, insufficient capacity, and weak monitoring and evaluation systems impeded the client's pursuit of enhanced municipal government services.